Relation between postoperative blood-aqueous barrier damage and LOCS III cataract gradings following routine phacoemulsification surgery - Ursell, P (1997)
AIM—To examine the relation between cataract density, the phacoemulsification energy required for its removal, and blood-aqueous barrier (BAB) damage on the first day after surgery. METHODS—A prospective study recruiting patients with normal eyes apart from senile cataract. Preoperatively, visual acuity, anterior chamber laser flare, and cell values were measured using the Kowa laser flare meter, and the LOCS III grading of the cataract defined. The patients all underwent standardised phacoemulsification surgery through a superior scleral tunnel incision, with confirmed in the bag placement of a one piece PMMA IOL; all surgical complications were excluded. The phaco power delivered was recorded as the cumulative delivered energy, CDE. On day 1 visual acuity and laser flare and cell readings were taken. RESULTS—101 patients were recruited and all completed the protocol. Older patients had a higher preoperative flare value (p=0.003); preoperative cell values were significantly related to nuclear opacity (p=0.021) and colour (p=0.011). Postoperative flare was related to preoperative flare (p=0.001) and nuclear colour (p=0.038). CDE was related to nuclear colour (p=0.031) and opacity (p=0.022), but not to aqueous flare. CONCLUSIONS—Damage to BAB after routine phacoemulsification surgery is predicted by the preoperative flare values and the density of the cataract nucleus. The amount of phacoemulsification energy required to remove a cataractous lens is related to the density of the cataract but affects postoperative flare to a minimal degree. Other factors such as surgical technique are probably more important. Laser photometry is a useful tool for objectively assessing surgical technique.